Visualization of halide perovskite crystal growth processes by in situ heating WAXS measurements. Issue 21 (17th February 2021) - Nakamura, Yuiga; Shibayama, Naoyuki; Sugimoto, Kunihisa
Abstract : We observed the crystallization dynamics of halide perovskite crystals (CH3 NH3 PbI3 ) by in situ heating WAXS measurements. Abstract : We observed the crystallization dynamics of halide perovskite crystals (CH3 NH3 PbI3 ) by in situ heating wide-angle X-ray scattering measurements. As a result, we revealed that crystal growth occurs during the conversion of complexes to perovskite crystals.